Who Governs the Village: Reconstructing Regulatory Authority over Village Affairs - Fathimah Azzahro; Hantoro, Bimo Fajar; Saputra, Bintar Abhi (Jurist-Diction, 2026)
This research examines the jurisdictional dualism between the Ministry of Home Affairs and the Ministry of Village caused by the ambiguous definition of 'Minister' in the Village Law. This study aims to answer two questions: (1) how is the regulatory authority over village affairs structured; and (2) what model of regulatory reconstruction is appropriate for governing these affairs? This study employs doctrinal legal research utilizing both statutory and conceptual approaches. The findings indicate that the Village Law’s ambiguous definition of “Minister” creates legal uncertainty and jurisdictional overlaps between the Ministry of Home Affairs and the Ministry of Village. Consequently, this research proposes two alternative solutions: (1) granting the Ministry of Village sole autonomy as the mandate holder for village sub-governmental affair; or (2) centralizing authority under the Ministry of Home Affairs. These findings emphasize the urgency of revising the definition of “Minister” and harmonizing implementing regulations to establish an integrated institutional framework, thereby ensuring bureaucratic efficiency and legal certainty.